Pengelolaan Supervisi Akademik Oleh Kepala Sekolah Di SD Negeri 6 Putatsari Kecamatan Grobogan - Sugiyanti, Mis Sugiyanti; , Prof. Dr. Sutama, M.Pd; , Dr. Sabar Narimo, M.M., M.Pd (2016)
This study aims to describe the planning, execution, and feedback/follow-up academic supervision principals in primary schools 6 Putatsari District of Grobogan. This research is qualitative. Qualitative research more emphasis on understanding and meaning, is closely related to specific values , more emphasis on the process rather than measuring, describing, interpreting , and gives meaning and not enough with the explanation alone, and utilize multimedia in research. Data collection techniques with interview, observation and documentation. Data analysis techniques to the analysis of the groove. The process of data collection through the reduction, display , and verification. The validity of the data using triangulation and source . Results of the study, 1) Planning academic supervision in SD Negeri 6 Putatsari produce, a. Preparation of schedule of supervision, b. Preparation of Instruments, c. Compile a list of teachers who would be supervised. 2) Implementation of supervision lasted three stages , namely, the initial planning stage , the implementation stage and the final stage of observation/evaluation. 3) Feedback supervision function in SD Negeri 6 Putatsari is to communicate the results of supervision to teachers as feedback to correct errors and deficiencies of learning , which is useful for developing its professionalism, so it will affect the quality of learning .